Development of a nursing diagnosis educational software program - Miriam de Abreu Almeida; Amália de Fátima Lucena; Aline Tsuma Gaedke Nomura; Murilo Graeff; Natália Chies; Lisiane Pruinelli (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Introduction The human-computer interaction is essential in simulated electronic systems associated with teaching-learning activities. Interactive clinical cases reinforce the diagnostic reasoning ability, a stage of the advanced Nursing Process. Purpose To build educational software, based on NANDA International, to improve the accuracy of nursing diagnoses. Method Methodological study in three stages: preparation and validation of case studies; construction; homologation and evaluation. Held between January / 2012 and December / 2013, in a university hospital in southern Brazil. Teachers, nurses, undergraduate students and graduate students in nursing and information technology participated. Approved by the Research Ethics Committee (130035). Results Construction of five case studies and two versions of the software: one simulates the reasoning process for establishing the diagnosis; another, aimed at teachers, makes it possible to edit/create cases. Conclusion The software helps in the teaching-learning process, generating accurate diagnoses, supporting more appropriate interventions.